Treadmill training of rats after sciatic nerve graft does not alter accuracy of muscle reinnervation - Barham, Mohammed; Andermahr, Jonas; Majczyński, Henryk; Sławińska, Urszula; Vogt, Johannes; Neiss, Wolfram F. (Frontiers in Neurology, 2023)
Background and purpose After peripheral nerve lesions, surgical reconstruction facilitates axonal regeneration and motor reinnervation. However, functional recovery is impaired by aberrant reinnervation. Materials and methods We tested whether training therapy by treadmill exercise (9 × 250 m/week) before (run–idle), after (idle–run), or both before and after (run–run) sciatic nerve graft improves the accuracy of reinnervation in rats. Female Lewis rats (LEW/SsNHsd) were either trained for 12 weeks (run) or not trained (kept under control conditions, idle). The right sciatic nerves were then excised and reconstructed with 5 mm of a congenic allograft. One week later, training started in the run–run and idle–run groups for another 12 weeks. No further training was conducted in the run–idle and idle–idle groups. Reinnervation was measured using the following parameters: counting of retrogradely labeled motoneurons, walking track analysis, and compound muscle action potential (CMAP) recordings. Results In intact rats, the common fibular (peroneal) and the soleus nerve received axons from 549 ± 83 motoneurons. In the run–idle group, 94% of these motoneurons had regenerated 13 weeks after the nerve graft. In the idle–run group, 81% of the normal number of motoneurons had regenerated into the denervated musculature and 87% in both run–run and idle–idle groups. Despite reinnervation, functional outcome was poor: walking tracks indicated no functional improvement of motion in any group. However, in the operated hindlimb of run–idle rats, the CMAP of the soleus muscle reached 11.9 mV (normal 16.3 mV), yet only 6.3–8.1 mV in the other groups. Conclusion Treadmill training neither altered the accuracy of reinnervation nor the functional recovery, and pre-operative training (run–idle) led to a higher motor unit activation after regeneration.